Thin Slices of Online Profile Attributes - and Counts, Scott (International Conference on Weblogs and Social Media (ICWSM), 2008)
People form consistent impressions of others given surprisingly little information. With the advent of social networks, impressions now may form online rather than in a face-to-face context. This research explores aspects of online impression formation and discusses the crucial role of user profiles in this process. By examining users’ decisions in an experimentally controlled social network, we show that users need only a “thin slice” of profile information in order to form impressions of others online. Additionally, specific profile attributes are evaluated for their perceived utility (how much do users choose to view these attributes), predictiveness (how well they serve as a proxy for a full profile), and diagnosticity (their ability to help users choose between online profiles). Findings provide design suggestions for better profile displays when space is restricted.